RELATIONSHIP BETWEEN INTERPERSONAL INTELLIGENCE AND EMOTIONAL INTELLIGENCE WITH TEACHER PERFORMANCE OF MTSN IN BANJARMASIN CITY - Hamid, Pahrudin Ali; Suriansyah, Ahmad; Ngadimun, Ngadimun (Journal of K6, Education and Management, 2019)
social environmental factors that contribute to Interpersonal Intelligence that will influence Emotional Intelligence and the performance of the teacher itself In carrying out its duties, the teacher is always faced with a variety of problems, both related to the main task as an educator which is continuing and developing life values, as well as a teacher that is continuing and developing science and technology, also the teacher as a trainer namely, developing skills the students, on the quality of teacher performance, one of them is reflected in the results of the first stage of the 2018 Teacher Competency Test data from the Banjarmasin City Education Office, of 142 teachers of the State Madrasah Tsanawiyah in Banjarmasin city, obtained an overall average value of 39.22. This is to find out the relationship between Interpersonal Intelligence and Emotional Intelligence with performance Madrasah Tsanawiyah Teachers of State in Banjarmasin City.The type of research used is explanatory with a quantitative approach. The conclusion of this study is the variable Interpersonal Intelligence of Madrasah Tsanawiyah teachers in the city of Banjarmasin has a high category, as well as the performance variable of Madrasah Tsanawiyah Negeri in Banjarmasin City. The analysis of the results of the study states that the relationship between Interpersonal Intelligence and teacher performance variables of Madrasah Tsanawiyah Negeri in Banjarmasin City is significant, with very strong categories, Emotional intelligence variables of Madrasah Tsanawiyah Negeri teachers in Banjarmasin City have high categories. Analysis of the results of the study states that the relationship between Emotional Intelligence and the performance of teachers of Public Madrasah Tsanawiyah in Banjarmasin City is significant, with a very strong category, Variables Interpersonal Intelligence and Emotional intelligence have a significant relationship with the performance of teachers of Public Madrasah Tsanawiyah in Banjarmasin City, with a very strong category .Suggestions put forward are as follows: For Schools, it is expected to increase the availability of school facilities and infrastructure, especially facilities for teachers in the implementation of the learning process and Teachers, are expected to improve their performance by building maximum Interpersonal intelligence and proper management of Emotional Intelligence.